over(MS, -) quark distribution and dipole scattering matrix elements at high energy - Hautmann, F; Soper, D (2008)
We discuss the operator relation that connects the renormalized quark distribution in the over(MS, -) scheme with the Wilson-line correlator representing dipole scattering in the s-channel picture. © 2008 Elsevier B.V. All rights reserved.